APLICACIÓN DE SISTEMAS DE CALIDAD EN LA ELABORACIÓN DE ALIMENTOS Y SERVICIOS AL CLIENTE PARA ESTABLECIMIENTOS DE EXPENDIO DE COMIDA NO CLASIFICADOS EN EL DISTRITO DE JESÚS MARÍA - Ugarte Casafranca, Walter David (2012)
In Peru there is a divorce between its rich cuisine and parameters or minimum quality standards to ensure optimum service in restaurants. The purpose of the application of HACCP Quality Plans is to create security seals in order to spread a new image quality Peruvian cuisine, and develop business management tools that improve consumer product. With this research we attempt to propose mechanisms to improve the service of restaurants, basing these mechanisms on HACCP international system, adapted to our reality and proposing the creation of guarantee seals for this establishments in Jesus Maria district.